2015
DOI: 10.1039/c5ta00970g
|View full text |Cite
|
Sign up to set email alerts
|

A new class of electroactive Fe- and P-functionalized graphene for oxygen reduction

Abstract: A new class of electroactive Fe- and P-functionalized reduced graphene oxide is prepared, which illustrates high ORR activity both in alkaline and acidic conditions due to its high surface area and formation of active Fe–P complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 59 publications
2
93
0
Order By: Relevance
“…198 experimentally; the obtained PG displayed a competitive ORR performance with an onset potential of 23.5 mV only (negatively shifted from that of Pt/C), n values higher than 3.6 and an extraordinary stability with 3.57 % current loss after 16 000 s. 135 Furthermore, Yu's group investigated the synergistic effect between P dopants and metal centres (Fe) in graphene materials for ORR, which generates the electrochemically active Fe-P species. 199 Interestingly, PG becomes active in acidic medium due to the excellent blend of Fe and P functionalization and improved active surface area. value, whereas an ortho B atom directly bonded to N as BN having the lowest activity owing to the lack of the C bridge (Figure 9f).…”
Section: Pg Based Catalystsmentioning
confidence: 99%
“…198 experimentally; the obtained PG displayed a competitive ORR performance with an onset potential of 23.5 mV only (negatively shifted from that of Pt/C), n values higher than 3.6 and an extraordinary stability with 3.57 % current loss after 16 000 s. 135 Furthermore, Yu's group investigated the synergistic effect between P dopants and metal centres (Fe) in graphene materials for ORR, which generates the electrochemically active Fe-P species. 199 Interestingly, PG becomes active in acidic medium due to the excellent blend of Fe and P functionalization and improved active surface area. value, whereas an ortho B atom directly bonded to N as BN having the lowest activity owing to the lack of the C bridge (Figure 9f).…”
Section: Pg Based Catalystsmentioning
confidence: 99%
“…[21][22][23] Recently, phosphorus, which is a group 15 heteroatom (located in the same group as N) with similar chemical properties as nitrogen, has attracted considerable attention. [24][25][26] Due to the difference in diameter and electronegativity, P-doping of carbon materials exhibit a vast difference against the N element. The theoretical calculation confirmed that P doping of carbon material has higher electron-donor properties, higher adsorption for O 2 , and higher oxidation potential than the N atom, 27,28 suggesting that P doping of carbon is a promising ORR catalyst.…”
mentioning
confidence: 99%
“…The HPSs were thermally treated at 650 • C for 3 h with a heating rate of 2 • C min −1 in NH 3 atmosphere at a gas flow rate of 40 sccm to obtain NHCSs.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In recent years, fuel cells have been attracting lots of attention due to their high energy conversion efficiency for converting chemical energy into electricity [1][2][3][4][5]. The entire reaction process occurring in fuel cells contains two half-reactions; one is the oxygen reduction reaction (ORR) at the cathode and the other is the hydrogen oxidation reaction (HOR) taking place at the anode.…”
Section: Introductionmentioning
confidence: 99%